KONTRIBUSI BUDAYA PERUSAHAAN DAN MORAL KERJA TERHADAP KINERJA KARYAWAN - RR. NIKEN PURBASARI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The background of this research is the idea that successful organizational is having a role in increasing performs of employees. Performance is what people achieve and how they achieve it. The high performance is influenced by the strong and adaptability culture and high work morale. The culture can create a high morale foundation. Organizational culture exist to explain the values that were distributed, the principles, traditions and ways of doing things, which affect how members organization act in running the organization, and work morale means the attitude of individuals and groups toward their work environment and toward voluntary cooperation to give the full extent of their ability in the best interest of the organization. The limited question of this research is there any contributions between: corporate culture with employee performance, corporate culture with work morale, work morale with employee performance, corporate culture and work morale with employee performance. The design of this research applies survey method with marketing employees of banking institutions in Jakarta. The method of this research is using path analysis. The result showed that there is significant contribution between : (1) corporate culture and employee performance, (2) corporate culture and work morale, (3) work morale and employee performance (4) corporate culture and also work morale with employee performance. Corporate culture through the work of morale formation is more dominant contribution to employee performance. The background of this research is the idea that successful organizational is having a role in increasing performs of employees. Performance is what people achieve and how they achieve it. The high performance is influenced by the strong and adaptability culture and high work morale. The culture can create a high morale foundation. Organizational culture exist to explain the values that were distributed, the principles, traditions and ways of doing things, which affect how members organization act in running the organization, and work morale means the attitude of individuals and groups toward their work environment and toward voluntary cooperation to give the full extent of their ability in the best interest of the organization. The limited question of this research is there any contributions between: corporate culture with employee performance, corporate culture with work morale, work morale with employee performance, corporate culture and work morale with employee performance. The design of this research applies survey method with marketing employees of banking institutions in Jakarta. The method of this research is using path analysis. The result showed that there is significant contribution between : (1) corporate culture and employee performance, (2) corporate culture and work morale, (3) work morale and employee performance (4) corporate culture and also work morale with employee performance. Corporate culture through the work of morale formation is more dominant contribution to employee performance.